Analisis Faktor-Faktor yang Mempengaruhi Intensi Penggunaan M-Tix Sebagai Layanan Pembelian Tiket Menonton Film Bioskop Jaringan Cinema XXI Indonesia: Pendekatan Technology Acceptance Model (TAM) - KUSNO, Adi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to analyze the factors that affect to use intention of e- ticketing services provided by Cinema XXI to its customers. These factors were taken from the dimensions of Technology Acceptance Model (TAM) in the form of perceived ease of use, perceived usefulness, and subjective norm. Data analysis was performed with Structural Equation Modeling (SEM). The applications that are used to analyze the data is AMOS 19. The respondents of this research were some customers of Cinema XXI who know about M-Tix. The result of this research showed that (1) use intention of M-Tix influenced by perceived ease of use and perceived usefulness, (2) perceived ease of use have effect on perceived usefulness, (3) subjective norm have effect on perceived usefulness, (4) subjective norm have no effect on use intention of M-Tix when system use is perceived to be voluntary.